The Impact of Parental Emotional Availability on Academic Outcomes - Awawda, Jumana Sobhi; Bashir, Yasir Riad (Journal of Posthumanism, 2025)
This study examines the influence of parental emotional availability on students’ academic performance. Drawing on data collected from 50 parents across diverse socioeconomic backgrounds, the research explores how emotional bonding between parents and children contributes to educational development. The findings reveal that students tend to achieve higher academic outcomes when their parents demonstrate consistent emotional presence, characterized by support, empathy, and active involvement. Parents reported that emotional support within the family fosters increased motivation, enhanced stress management, and more positive relationships with teachers. The study also underscores the role of socioeconomic status in shaping how emotional support is provided and experienced. Ultimately, the emotional engagement of parents plays a pivotal role in shaping students’ academic experiences and performance.